Health-related quality of life and associated factors among epilepsy patients in sub-Saharan Africa: a systematic review and meta-analysis - Beyene, Dessale Abate; Demsie, Desalegn Getnet; Tafere, Chernet; Yazie, Taklo Simeneh; Endeshaw, Destaw; Tadesse, Tamrat Assefa; Addisu, Zenaw Debasu (Frontiers in Neurology, 2025)
BackgroundEpilepsy is a major public health issue worldwide, often leading to physical and cognitive impairments that limit employment, independence, and social interaction. Health-related quality of life (HRQoL) is a crucial outcome in the treatment of chronic epilepsy as it is linked to reduced independence, treatment challenges, and lower life expectancy. HRQoL serves as an important health indicator for assessing the impact of the disease on daily living activities.ObjectiveThis study aimed to estimate the mean score of health-related quality of life (HRQoL) and factors associated with lower HRQoL in people living with epilepsy (PLWE) in sub-Saharan African (SSA) countries.MethodsA comprehensive literature search was conducted using PubMed, Cochrane Library, Scopus, and Google Scholar databases. This review has been registered with PROSPERO (CRD42024620363). The eligibility criteria were established, and this review included cross-sectional and observational studies assessing HRQOL in PLWE in SSA countries, published in English from the inception of databases through November 2024. The pooled HRQoL was reported as the mean score with accompanying 95% confidence intervals. Finally, publication bias was evaluated using a funnel plot and Egger’s regression test.ResultsThe pooled mean score of HRQoL among PLWE in SSA was 63.79 (95% CI: 59.75–67.84%). Owing to significant heterogeneity across the studies, a random-effects model was utilized for the meta-analysis (I2 = 98.96%, p < 0.001). This meta-analysis indicated that anxiety (β = −4.762, p = 0.0029), depression (β = −4.591, p < 0.0001), uncontrolled seizures (β = −4.321, p < 0.0001), and a family history of epilepsy (β = −5.093, p = 0.0013) had statistically significant negative impacts on HRQoL in PLWE. Despite some asymmetry in the funnel plot, Egger’s test showed no significant publication bias, with a p-value of 0.321.ConclusionThis review found a moderate pooled mean score of HRQoL among PLWE in SSA countries. Factors that negatively affect HRQoL in these regions include anxiety, depression, uncontrolled seizures, comorbidities, and a family history of epilepsy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/search, identifier CRD42024620363.